2003
DOI: 10.1081/pln-120024266
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Binding Properties of TTf, a Salt‐Induced Transferrin from the AlgaDunaliella salina

Abstract: Iron deficiency induces accumulation of a transferrin-like protein, TTf, in plasma membranes of the halotolerant alga Dunaliella salina. In vivo iron binding and uptake studies provided evidence for the role of TTf in iron acquisition in Dunaliella. In this report, we characterized the iron binding activity of solubilized TTf, purified from plasma membrane vesicles of iron-starved cells. The characteristics of iron binding to TTf generally resembled those of animal transferrins (Tfs) in an obligatory requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…The observation that D. salina cells contain prebound iron that is not removed by extensive washing is consistent with the high binding affinity of D. salina TTf for Fe 31 ions that we reported in previous studies None 0.9 6 0.2 (100) 3.8 6 0.6 (100) 2Bicarbonate 0.1 6 0.05 (10) 0.5 6 0.15 (13) (Fisher et al, 1998;Schwarz et al, 2003b Figure 3 and Table III, there is less than 10% exchange within 1 h at 4°C. The bound iron can be stripped off effectively by EDTA and, to a lesser extent, at acidic pH.…”
Section: Tightly Bound Iron Exchanges Slowly With Medium Fe 31supporting
confidence: 68%
See 3 more Smart Citations
“…The observation that D. salina cells contain prebound iron that is not removed by extensive washing is consistent with the high binding affinity of D. salina TTf for Fe 31 ions that we reported in previous studies None 0.9 6 0.2 (100) 3.8 6 0.6 (100) 2Bicarbonate 0.1 6 0.05 (10) 0.5 6 0.15 (13) (Fisher et al, 1998;Schwarz et al, 2003b Figure 3 and Table III, there is less than 10% exchange within 1 h at 4°C. The bound iron can be stripped off effectively by EDTA and, to a lesser extent, at acidic pH.…”
Section: Tightly Bound Iron Exchanges Slowly With Medium Fe 31supporting
confidence: 68%
“…Moreover, we found that isolated TTf from D. salina has very similar Fe 31 -binding parameters as intact cells and that dissociation of TTf from plasma membranes completely eliminated Fe-binding activity to TTf-deficient membranes (Schwarz et al, 2003b (Fisher et al, 1997(Fisher et al, , 1998. As shown in Table II, iron-deficient cells display a higher affinity for both iron and bicarbonate, suggesting changes in properties of the iron-binding sites.…”
Section: Dunaliella Cells Contain Externally Bound Ironmentioning
confidence: 73%
See 2 more Smart Citations
“…The iron-binding transferrin-like protein Ttf is a surface-associated protein that has been well characterized in our laboratory as a mediator of iron uptake (30,31).…”
Section: Functional Classification Of Identified Proteinsmentioning
confidence: 99%